CROSS-SECTION STUDIES OF THE CONSUMPTION OF AUTOMOBILES IN THE UNITED STATES - Bennett, W. Burr (American Economic Review, 1967)
THIS IS A STUDY OF THE CONSUMPTION OF AUTOMOBILES IN THE UNITED STATES DURING THE PERIOD 1955-57. DEPRECIATION IS USED AS THE PRIMARY MEASURE OF CONSUMPTION IN ORDER TO DETERMINE HOW WELL DEMAND MEASURED IN THIS WAY CAN BE EXPLAINED BY INCOME AND OTHER SOCIAL AND DEMOGRAPHIC VARIABLES. THIS STUDY DIFFERS FROM EARLIER WORK IN THREE RESPECTS: THE LIMITED DEPENDENT VARIABLE MODEL DEVELOPED BY TOBIN IS USED IN ORDER TO HANDLE CORRECTLY THE PROBLEM OF ZERO EXPENDITURE HOUSEHOLDS. THE DATA USED ARE DRAWN FROM THE SURVEYS OF CONSUMER FINANCES FOR THE YEARS 1955, 1956, AND 1957. THE ESTIMATES FOR EACH OF THE YEARS ARE COMPARED AND APPEAR TO BE REASONABLY CONSISTENT. A REPAIR COST BASED ON THE AGE OF EACH CAR IS INCLUDED IN THE TOTAL COST INCURRED BY THE HOUSEHOLD. THE CONCLUSIONS ARE THAT: (1) HOUSEHOLD CONSUMPTION RISES WITH INCOME, BUT RISES LESS SHARPLY AT HIGHER THAN AT LOWER INCOMES, (2) EXPENDITURE DECREASES AS THE HEAD OF THE HOUSEHOLD APPROACHES RETIREMENT AGE, (3) EXPENDITURE INCREASES AS THE NUMBER OF ADULTS IN THE SPENDING UNIT INCREASES, (4) EXPENDITURE DECREASES AS THE NUMBER OF CHILDREN INCREASES, (5) AFTER ADJUSTMENT FOR OTHER FACTORS, SPENDING UNITS LIVING IN NEW YORK AND CHICAGO SHOW LOWER THAN AVERAGE, AND THOSE LIVING IN RURAL AREAS SHOW HIGHER THAN AVERAGE CONSUMPTION, (6) NONWHITE SPENDING UNITS CONSUME CARS AT A LOWER LEVEL THAN WHITE. /AUTHOR/